ERRATUM - Urszula Ledzewicz; Andrzej Swierniak (Mathematical Biosciences and Engineering)
In the paper ''Spatially Distributed Morphogen Production and Morphogen Gradient Formation' by Arthur D. Lander, Qing Nie, and Frederic Y. M. Wan (Mathematical Biosciences and Engineering, Volume 2, Number 2, April 2005), the following correction should be made:In the statement of Lemma 10, '(0,1)' should hav been '($-x_m$, 1).'